1948
DOI: 10.1108/eb026133
|View full text |Cite
|
Sign up to set email alerts
|

Bradford's Law of Scattering

Abstract: DURING the course of an analysis of some 1,600 periodical references, borrowed by the library of Butterwick Research Laboratories from outside libraries, the results of the analysis were compared with studies on the scatter of articles in periodicals carried out at the Science Library. These were originally published in the journal Engineering, vol. cxxxvii, p. 85, 26 Jan. 1934, and were recently summarized by S. C. Bradford in his book, Documentation (London: Crosby Lockwood and Son, Ltd., 1948). A certain mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
7

Year Published

1978
1978
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(65 citation statements)
references
References 0 publications
4
54
0
7
Order By: Relevance
“…This analysis showed that the numbers of ORG and AGR publications had very similar doubling times during the last decades. Furthermore, Siegmeier et al (2014a, b) showed that the generally expected exponential pattern in the distribution of scientific publications (Vickery 1948) holds true for ORG publications. Exponential patterns were revealed concerning authors, countries of origin, author affiliations and journals.…”
Section: Publications On Organic Agriculturementioning
confidence: 99%
“…This analysis showed that the numbers of ORG and AGR publications had very similar doubling times during the last decades. Furthermore, Siegmeier et al (2014a, b) showed that the generally expected exponential pattern in the distribution of scientific publications (Vickery 1948) holds true for ORG publications. Exponential patterns were revealed concerning authors, countries of origin, author affiliations and journals.…”
Section: Publications On Organic Agriculturementioning
confidence: 99%
“…Por eso, es necesario buscar métodos alternativos para medir la productividad como una herramienta para la toma de decisiones en la adquisición. En adición, algunos científicos de la información han estado últimamente más preocupados con la formulación matemática de la ley, y aún insisten en discutir si esta formulación matemática se ajusta a la observación gráfica o aun si tiene un carácter científico (Vickery, 1948;Brookes, 1969). Otros autores han propuesto variaciones en el modelo, tales como la distribución jerárquica (Basu, 1992), mientras que otros han desarrollado rangos sectorizados (Sivers, 1987).…”
Section: Revisión De La Literaturaunclassified
“…Vickery extended the verbal formulation to show that it applied to any number of zones of equal yield, not to only the three zones that Bradford had used for his data. 12 Later Leimkuhler expressed the verbal formulation mathematically as is shown in equation 1.13 where…”
Section: Introductionmentioning
confidence: 99%